EGNOS e l’aviazione civile - Bernardini, Fabrizio; Pezzella, Carmine (GEOmedia, 2010)
EGNOS and the civil aviation This article continues the series about Global Navigation Satellite Systems, and discusses in more depth the main use for EGNOS: providing augmentation signals for the European region. EGNOS complete availability, starting next February, will be a major milestone toward the full utilization of the system to improve flight procedures (mainly in the approach phase), optimizing traffic flows and increasing air transport safety.